The High-fidelity clinical simulation with performance and virtual simulation in a metaverse as strategies for the training of future doctors. - Charry Cuellar, Jose Daniel (Spanish Journal of Medical Education, 2026)
Introduction: High-fidelity clinical simulation with standardized patients and virtual simulation in immersive environments such as the metaverse have emerged as complementary educational strategies. Methodology: A qualitative systematic literature review was conducted according to PRISMA 2020 guidelines. The search was performed in Medline (PubMed), Scopus, and Google Scholar (2020–2025). The PICO question was used to structure the search, with MeSH terms such as "high-fidelity simulation," "standardized patients," "metaverse," and "medical education." Methodological quality was assessed using the Cochrane risk of bias scale and the SIGN levels of evidence. Results: 4,301 records were identified, of which 7 met the inclusion criteria. Both approaches demonstrated effectiveness in developing technical and non-technical skills, although with different strengths. Role-playing simulation stood out for its ability to train practical clinical skills, decision-making under pressure, and communication skills, while metaverse simulation showed advantages in accessibility, scalability, repeatability of learning, and immersive visualization of complex physiological processes. The evidence presented a low to moderate risk of bias, with a level of evidence 1+ to 2+ according to SIGN. Conclusions: Role-playing simulation is a highly effective tool for recreating complex clinical scenarios with emotional realism and spontaneity, aspects difficult to replicate using current digital technologies. In contrast, metaverse simulation offers benefits in terms of accessibility, scalability, and repeatability of learning. Integrating both methodologies represents the most appropriate strategy for contemporary medical education, allowing for comprehensive training that combines the development of clinical competencies with human sensitivity and the use of technological innovation. Specific educational implications for hybrid curriculum design are proposed.